"I Will Try My Best to Make It Worth It": Robert Venturi's Road to Rome. Issue 2 (2nd July 2016) - Costanzo, Denise R.
Abstract : Robert Venturi's Rome Prize fellowship (1954–56) is a familiar, pivotal episode in his early career. But why did he want to go to the American Academy in the early 1950s? Venturi approached his fellowship with rare determination at a time when modernism made the Rome Prize's architectural relevance unclear. What made him certain this opportunity would be the key to his success, and how did this influence the book he published a decade later? As Complexity and Contradiction in Architecture marks its fiftieth anniversary, clarifying why Venturi valued the Rome Prize further illuminates his views on history, context, and meaningful design.